Direct evidence of a high-concentration basal layer in a submarine turbidity current. (July 2020) - Wang, Zhiwen; Xu, Jingping; Talling, Peter J.; Cartigny, Matthieu J.B.; Simmons, Stephen M.; Gwiazda, Roberto; Paull, Charles K.; Maier, Katherine L.; Parsons, Daniel R.
Abstract: Submarine turbidity currents are one of the most important sediment transfer processes on earth. Yet the fundamental nature of turbidity currents is still debated; especially whether they are entirely dilute and turbulent, or a thin and dense basal layer drives the flow. This major knowledge gap is mainly due to a near-complete lack of direct measurements of sediment concentration within active submarine flows. Here we present the most detailed near-bed sediment concentrations measurements from a powerful turbidity current in Monterey Canyon, offshore California. We employ a novel approach using correlations between conductivity and sediment concentration, which unlike previous methods can measure very high concentrations and not sensitive to grain size. We find that sediment concentrations close to the canyon floor gradually increased after the arrival of the turbidity current, until reaching a maximum value of 12%, the highest concentration ever inferred from direct measurements in turbidity currents. We also show a two-layer flow head, with a fast (up to 4 m/s), thin and dense basal layer overlain by a thicker ( 50 m) dilute flow. At the interface of these two layers, there seems to be a sharp steep concentration gradient. Such quantitative measurements of sediment concentration can produce a key step forward in understanding the basic character and dynamics of these powerful submarine flows. Highlights: Very high sediment content can reduce the conductivity of turbid water. Archie's law can be used to estimate super-high sediment concentrations. Concentration in the dense basal layer of the turbidity current was as high as 12%.